2019
DOI: 10.1002/2211-5463.12610
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic pattern of breast milk discriminates obese mothers with infants of delayed weight gain from normal‐weight mothers with infants of normal weight gain

Abstract: We previously reported that exclusively breastfed infants born to mothers with pregestational obesity gain less weight during the first month after birth than those born to mothers of normal pregestational weight. This issue is potentially important since lower weight gain in breastfed infants of obese mothers might increase the risk of developing later obesity. Breast milk quality and quantity, together with breastfeeding practice, possibly influence infants’ feeding behavior, appetite control, and regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Other research purports a differential effect of leptin and adiponectin concentrations in breast milk on the development of infant lean and fat mass in the first year of life [ 55 ]. Further, secretory immunoglobulins are also thought to play a major role in breast milk mediated modulation of infant body composition [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other research purports a differential effect of leptin and adiponectin concentrations in breast milk on the development of infant lean and fat mass in the first year of life [ 55 ]. Further, secretory immunoglobulins are also thought to play a major role in breast milk mediated modulation of infant body composition [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…One such factor may be obesity, which has been linked with systematic low-grade inflammation [6,7] and further maternal obesity with an increased risk of various complications for both foetus and neonate [8]. A recent study found 15 proteins differently expressed in breast milk of obese women as compared to those with normal weight [9].…”
Section: F I G U R Ementioning
confidence: 99%